Landscape Ecology in Theory and Practice Pattern and Process - Turner, Monica Goigel; Gardner, Robert H. 1941-; O'Neill, Robert V. 1940- (Springer New York, 2001)
Landscape ecology is not a distinct discipline or simply a branch of ecology, but rather is the synthetic intersection of many related disciplines that focus on the spatial-temporal pattern of the landscape. Risser et al. , 1984 The emergence of landscape ecology as a discipline has catalyzed a shift in paradigms among ecologists, . . . resource managers and land-use planners. Having now seen the faces of spatial pattern and scale . . . we can never go back to the old ways of viewing things. Wiens, 1999 his book presents the perspective of three ecologists on the concepts and Tapplications of landscape ecology, a discipline that has shown expansive growth during the past two decades. Although landscape ecology is a multidis- plinary subject involving components as diverse as economics and sociology, the earth sciences and geography, remote sensing and computer applications, we - cus here on what ecologists need to know about landscapes. Landscape ecology served as the integrating theme of our collaborative research for nearly 15 years, including a 7-year period during which we worked together at Oak Ridge National Laboratory. We became acquainted in January 1986 at the first annual United States Landscape Ecology symposium held at the Univ- sity of Georgia and organized by Monica Turner and Frank Golley. Landscape ecology was, at that time, a new subject in the United States. The first U. S.